(untitled) (El-Wahat Journal for Research and Studies, 2022)
ملخص : يتناول البحث دراسة تفصيلية للقاعدة الفقهية المشهورة: «إذا ضاق الأمر اتسع وإذا اتسع ضاق»، كما يتناول مسألة تغيير شرط الواقف باعتبارها قضية من أهم المسائل المطروحة في القطاع الوقفي، ثم يتناول علاقة القاعدة بهذه المسألة ووجه ارتباط القاعدة بهذه القضية؛ إذ القاعدة في مدلولها ترسم حدود هذا التغيير من جهة التوسع في ذلك والتضييق فيه. كلمات دالة: قاعدة، ضاق الأمر، اتسع الأمر، تغيير شرط الواقف. Abstract: This research presents a detailed study of the well-known jurisprudential rule: “If a matter narrows it is widened, and if it widens it is narrowed”. The study also deals with the issue of changing the conditions of the endower, which is one of the most important issues raised in the endowment sector. We investigate the relation between the above jurisprudential rule and this issue as the rule in its implication delineates the boundaries of this change in terms of its expansion or narrowing. Key words: : Jurisprudential rule, a matter narrows, a matter widens, changing the conditions of the endower.